A new Automated Behavioural Response system to integrate playback experiments into camera trap studies. Issue 8 (3rd January 2017) - Suraci, Justin P.; Clinchy, Michael; Mugerwa, Badru; Delsey, Michael; Macdonald, David W.; Smith, Justine A.; Wilmers, Chris C.; Zanette, Liana Y.
Summary: How animals respond to anthropogenic disturbances is a core component of conservation biology and how they respond to predators and competitors is equally of central importance to wildlife ecology. Camera traps have rapidly become a critical tool in wildlife research by providing a fully automated means of observing animals without needing an observer present, permitting data to be collected on rare or elusive species and infrequent events. Snapshots from camera traps revealing a species' presence have been the principal data used to date to gauge behaviour; but, lacking experimental controls, such data permit only correlational analyses potentially open to confounding effects. Playback experiments provide a powerful means to directly test the behavioural responses of animals, enabling strong inferences and rigorous conclusions not subject to the potential confounds affecting the interpretation of snapshot data; the principal factor to date limiting the use of playback experiments being the need to have an observer present. We developed an Automated Behavioural Response system (ABR) comprising a custom‐built motion‐sensitive speaker system that can be paired with any commercially available camera trap, providing the means to conduct playback experiments directly testing the behavioural responses of any species that can be 'caught' on a camera trap. We describe field tests in Uganda, Canada and the USA, experimentally testing the effects of anthropogenic disturbances and interactions among large carnivores, in species as diverse as elephants, black bears, chimpanzees and cougars; experiments that would be completely infeasible without the ABR. We evaluate factors affecting the rate of successful data collection in the experiments in Uganda and Canada, and detail how we maximized the system's performance in the USA experiment. By integrating the power playback experiments provide to directly and rigorously test behavioural responses with the capacity camera trapping affords to study virtually any animal anywhere, the ABR can both greatly expand the range of research questions addressed by conservation biologists and wildlife ecologists and qualitatively improve the rigour of the resulting conclusions. We discuss various ways to optimize the ABR's performance in any circumstance, and the many novel research opportunities made available by this new methodology.